“Evaluación de la concentración de material particulado pm 2,5 y pm10 en el terminal terrestre del cantón Salcedo de la provincia de Cotopaxi”. - Jaya Lema, Jhomayra Lisbeth (2024)
Human actions usually have consequences in the atmosphere causing the emission of particulate matter and gases that can affect health. This research report aims to evaluate particulate matter PM2.5 and PM10, with the purpose of mitigation strategies in the Salcedo Terrestrial Terminal of the Cotopaxi Province. For which, a direct observation of the place was carried out; establishing a methodology for the determination of suspended particles, where the level of contamination was analyzed, through the modality of a field visit, establishing 3 strategic points for monitoring, using the E-BAM equipment that is based on a radiation methodology. Beta, which measures the increase in weight of the particulate material as it is deposited in a filter according to the material being analyzed and the data is automatically collected for a period of 24 hours, as established by the Regulations TULSMA, these values must be analyzed and compared with Annex 4 of Book VI of the Unified Text of Environmental Legislation, where the maximum permissible limits established by current legislation are 100 μg/m3 for PM10 and 50 μg/m3 for PM2.5 . The results of the various samples indicated the low presence of contamination levels, but it can be observed that in some hours of the different monitoring days there were hours where it was higher than the others, for different reasons such as lunch time or departure of the terminal workers, but nevertheless they are below the maximum permissible limits. Finally, five proposals were made to maintain low pollution levels.